2023
DOI: 10.1123/ijsnem.2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Delayed Evening Meal Enhances Sleep Quality in Young Rugby Players

Abstract: The aim of this study was to examine the effect of delayed evening mealtime on sleep quality in young athletes. Twelve rugby players (age 15.8 ± 0.7 years) participated in a crossover within-participant design. Adolescents spent five consecutive days in each of two conditions, separated by a 2-week washout period: routine dinner (3.5 hr before bedtime) and late dinner (LD, 1.5 hr before bedtime). Other mealtimes as well as bedtime and wake-up time were usual and remained the same in both conditions. Their sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies reporting sleep findings in secondary school boarding students are limited. Typically, sleep has been a secondary focus (Boergers et al, 2014; Chan et al, 2018; Clarisse et al, 2010; Owens et al, 2010; Simpson et al, 2021) with only a limited pool directly examining sleep (Hedin et al, 2020; Kalak et al, 2019; Lehmann et al, 2022; Mander & Lester, 2021; Oluka et al, 2019). Of the studies which have directly examined sleep, only Kalak et al (2019) have compared boarding with day‐students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting sleep findings in secondary school boarding students are limited. Typically, sleep has been a secondary focus (Boergers et al, 2014; Chan et al, 2018; Clarisse et al, 2010; Owens et al, 2010; Simpson et al, 2021) with only a limited pool directly examining sleep (Hedin et al, 2020; Kalak et al, 2019; Lehmann et al, 2022; Mander & Lester, 2021; Oluka et al, 2019). Of the studies which have directly examined sleep, only Kalak et al (2019) have compared boarding with day‐students.…”
Section: Discussionmentioning
confidence: 99%
“…A single study found that early and middle but not late adolescent boarding compared to day‐students report a higher frequency of sleep problems but surprisingly longer sleep periods (Kalak et al, 2019). A further single study found that delaying dinner times improved sleep quality (Lehmann et al, 2022). A final single study reported that more than a half of the students at a Ugandan boarding school met clinical criteria for poor sleep quality with the highest frequency in boys (Oluka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms that may explain the effect of diet on sleep regulation are complex, this effect may be due to a particular dietary component, a metabolite, or long-term nutritional factors (Gérard & Vidal, 2019;Irwin et al, 2016;Shilo et al, 2002). In particular, the timing of meals and their influence on sleeping quality are interesting and the number of studies in this area are very few and have been designed on different populations (Falkenberg et al, 2021;Lehmann et al, 2022;Peuhkuri et al, 2012). Two investigations on healthy men' s carbohydrate intake before going to bed were carried out by Afaghi et al High or low GI meals were given 4 hours and 1 hour before bed in the first research.…”
Section: Introductionmentioning
confidence: 99%